Kestävän kehityksen periaatteet kielenoppimisen arvioinnissa - Laine Päivi; Maijala Minna; Mäntylä Katja (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2025)
Sustainable development is included in curricula in many countries – from primary to tertiary education, as well as in teacher training. Its principles also encompass language teaching, e.g., through enhancing equality of languages, multilingualism and multiculturalism. Several ethical issues are linked to sustainable development goals, which can be considered part of language teaching and assessment. Based on questionnaire data, this article addresses language teachers’ views on sustainable development and its connection to assessment of language learning. The results show that language teachers (N=29) do not recognize the link between assessment and teaching practices that follow sustainable development principles. Engagement and peer assessment seemed to be a way to support sustainable development principles in language teaching. Further, the results indicate that language teachers need more information about the effects of ethical assessment on supporting language learning and social sustainability.
Kielenoppimista tukeva arviointi: Assessment for supporting language learning